ANALYSIS OF THE IMPLEMENTATION OF GUIDANCE AND COUNSELING SUPERVISION AT STATE SENIOR HIGH SCHOOLS OF KUBU RAYA REGENCY - Abd Basith (Lembaga Penelitian UM Metro, 2016)
The objectives of this research are: (1) to describe and analyze the implementation of guidance and counseling supervision at the State Senior High Schools of Kubu Raya, and (2) to find main factors inhibiting the implementation of guidance and counseling supervisor at the State Senior High Schools of Kubu Raya regency. This study used the qualitative method with the interview as the data collection technique tested its validity through source triangulation. The research subjects in this study were one guidance and counseling supervisor and seven guidance and counseling teachers as the informants. The data analysis techniques used were data reduction, presentation, and conclusion. The results show that: (1) the implementation of the guidance and counseling supervision has still many weaknesses on each stage done by the supervisors, such as unidentified guidance and counseling teachers‘ needs, the program planning is not yet organized well, the supervisors do not use particular approaches, and they do not control the supervisions carried out, (2) some factors inhibiting the implementation of guidance and counseling supervision include lack of guidance and counseling supervision forces that so many guidance and counseling teachers are not supervised optimally, lack of knowledge and understanding by the supervisors on the implementation of the guidance and counseling supervision, and also minimal development of supervisory competencies in the guidance and counseling field.